PENGARUH DESAIN INTERIOR TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Restoran Lavenrice Bengkulu) - Ramadhan, Alman Fajar; Ratnawili, Ratnawili (UM. Bengkulu, 2024)
The title of this research is The Influence of Interior Design on Consumer Purchasing Decisions (Case Study on Lavenrice Bengkulu Restaurant Consumers)” just in time. This research influences the importance of purchasing decisions, several factors that influence purchasing decisions are Interior Design. This study aims to analyze the influence of interior design on consumer purchasing decisions at the Lavenrice Bengkulu Restaurant.